The Fundamental Assumption of Mr. Keynes' Monetary Theory of Unemployment - Leontief, Wassily W. (Quarterly Journal of Economics, 1936)
Journal Article The Fundamental Assumption of Mr. Keynes' Monetary Theory of Unemployment Get access Wassily W. Leontief Wassily W. Leontief Harvard University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 51, Issue 1, November 1936, Pages 192–197, https://doi.org/10.2307/1882507 Published: 01 November 1936